2015
DOI: 10.1007/s12012-015-9328-9
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Myocardial Impairment Occurred in Septal and Anterior LV Wall Segments After Anthracycline-Embedded Chemotherapy and did not Worsen During Adjuvant Trastuzumab Treatment in Breast Cancer Patients

Abstract: In a previous study of breast cancer patients, we found changes in cardiac function and size during the early stages of adjuvant trastuzumab (Herceptin(®)) therapy. Here we present a subgroup analysis of this patient cohort. This subgroup received a anthracycline-embedded chemotherapy followed by at least 3 months up to 6 months of adjuvant Herceptin(®) therapy. Twenty-seven female breast cancer patients with Her-2/-neu overexpression were studied using conventional echocardiography and 2D speckle tracking. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
1
9
0
7
Order By: Relevance
“…13 Our patient population was similar to those assessed in previous studies of cardiotoxicity in breast cancer patients, 14,15 suggesting that our data could be used to identify patients at high risk of developing CIC.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…13 Our patient population was similar to those assessed in previous studies of cardiotoxicity in breast cancer patients, 14,15 suggesting that our data could be used to identify patients at high risk of developing CIC.…”
Section: Discussionsupporting
confidence: 70%
“…19 This finding is also in agreement with a previous study that reported decreased longitudinal strain in septal, anteroseptal, anterolateral and apical segments in 27 patients undergoing chemotherapy with anthracyclines. 15 While it needs to be confirmed in further studies, recognition of this pattern of septal and anterior involvement may prove useful when screening for chemotherapy-related cardiotoxicity.…”
Section: Discussionmentioning
confidence: 97%
“…(2016 г.) показали увеличение степени митральной регургитации на фоне химиотерапии, особенно при лечении трастузумабом [5]. Было показано, что при лечении антрациклинами достоверно ухудшается диастолическая функция ЛЖ.…”
Section: двухмерная эхокардиографияunclassified
“…Главным ориентиром в оценке кардиотоксичности все же остается ФВ. Доказано, что ФВ ЛЖ снижается как на фоне химиотерапии [4,5,9], так и лучевой терапии [10]. Однако снижение ФВ ЛЖ наблюдается чаще на поздних сроках после химиотерапии.…”
Section: двухмерная эхокардиографияunclassified
“…A 2DSTE alkalmas lehet bizonyos esetekben kezelések (például kemoterápia) BK-ra kifejtett hatásának, esetleges mellékhatásainak vizsgálatára, továbbkövetéses vizsgálatok elvégzésére [27]. A módszer teoretikus előnye egyszerűsége, azonban hátránya, hogy csak egy adott síkban vizsgálja a BK-t.…”
Section: áBraunclassified